BASIS OF DEVELOPMENT OF THE SYSTEM FOR IMPLEMENTING THE MANAGEMENT OF TROOPS IN MODERN MILITARY CONFLICTS - Mukhliboev Muzaffar Makhmudovich; Sagitov Ravil Rafkatovich (American Journals, 2023)
In this article, important materials based on our national values, which are necessary for the educational process of military personnel serving in the armed forces of Uzbekistan, are included.
Keywords: National Guard, safe zone, alternative service, modern standards, defense industry, military conflict, armed conflict, military aggression, outsourcing system.